Pengaruh Model Pembelajaran Peer Teaching terhadap Minat dan Pemahaman Belajar Siswa pada Materi Persebaran Flora dan Fauna Dunia Kelas XI SMAN 1 Srengat - Yohana Ramadhanila Mayori; Hendra Pratama (Politeknik Kampar, 2025)
This research is based on low learning interest and low learning understanding at SMAN 1 Srengat. In the observation results, low interest is caused by the lack of student interest and attention to learning and the lack of student involvement in asking and commenting on geography lessons has an impact on students' lack of understanding of the material in the lesson Types of quantitative research Quasi Experiments. The results of this study show that 1) the peer teaching learning model has an effect on students' interest in learning in the distribution of world flora and fauna in class XI SMAN 1 Srengat, as evidenced by the acquisition of Sig.(2-tailed) score of 0.000 < 0.05, then Ha is accepted and H0 is rejected. 2) The peer teaching learning model has an effect on students' learning understanding on the distribution of world flora and fauna in class XI of SMAN 1 Srengat, as evidenced by the acquisition of Sig.(2-tailed) score of 0.000 < 0.05, then Ha is accepted and H0 is rejected.